Community intervention programmes with people affected by leprosy: Listening to the voice of professionals. - Gema Martos-Casado (PLoS Neglected Tropical Diseases, 2022)
Background Community participation and implementing interventions based on the community are key strategies to eliminate leprosy. Health professionals have an essential role as they are a necessary source of information because of their knowledge and experience, as well as their comprehensive perspective of contexts included in the programmes. This study has the aim of analysing the perceptions on the development of programmes with people affected by leprosy from the perspective of professionals that work at different organisations in endemic contexts. Methodology A qualitative study was carried out with the written response to an open question questionnaire which was sent by email. The script content was related to positive aspects and difficulties in daily work, participation from the community in activities, contribution to gender equality and programme sustainability. 27 health professionals were interviewed, 14 women and 13 men, all of which belonged to 16 organisations in India and Brazil. Once the content of the interviews was analysed, two main topics emerged: barriers perceived by professionals and proposals to improve the sustainability of the programmes. Principal finding Professionals identify barriers related to social stigma, inequalities, gender inequalities, difficulty managing the disease, limited services, lack of resources and lack of community participation. Furthermore, some necessary recommendations were taken into account to improve programme development related to: Eliminating stigma, reaching gender equality, developing adequate and effective services, guaranteeing adequate and quality resources and achieving compassion among professionals. Conclusions Although introducing community programmes with people affected by leprosy has a long history in countries such as India and Brazil, there are still several barriers that can hinder their development. Based on the specific needs of the contexts, recommendations are suggested that, with the involvement of all parties and with sensitive approaches towards human rights and gender, they could help to guarantee universal health coverage and the sustainability of said programmes.